"Grammarly" sebagai Asisten Penulisan Bahasa Inggris dari Perspektif Siswa EFL - Armanda, Muhamad Laudy; Nugraheni, Annisrina Fajri; Wulansari, Atsani; Imron, Ali (English Education:Journal of English Teaching and Research, 2022)
Automated Writing Evaluation (AWE) has been regarded as a viable pedagogical approach that utilizes technology to assist EFL students' writing. Writing becomes one of the important skills in English at any proficiency level. Hence, this study aimed to determine what EFL students thought about using Grammarly to check their work for grammar errors. Moreover, this research also describes the students’ frequency in using Grammarly to improve their writing. This study used descriptive qualitative methods to explore the students’ perspective in using Grammarly to check their work for grammar when writing articles. In addition, this study used non-probability sampling employing a purposive sampling technique. To assess the perception, researchers tracked 40 EFL students using a close-ended questionnaire with five indicators of Likert scale. At the same time, interviews were used as data triangulation. According to the results, most EFL students have a favorable view of utilizing Grammarly as an online grammar checker to assist them in writing articles. As an English writing helper, evidence showed that Grammarly could check for grammatical and stylistic errors. This study has thus far shed light on the good and bad aspects of utilizing Grammarly among EFL students. In general, EFL students think Grammarly's capabilities help write an article.